HOXC13-AS accelerates cell proliferation and migration in oral squamous cell carcinoma via miR-378g/HOXC13 axis. (December 2020) - Li, Wenlu; Zhu, Qiuyu; Zhang, Sanke; Liu, Lei; Zhang, Han; Zhu, Dandan
Highlights: HOXC13-AS was upregulated in OSCC and silencing HOXC13-AS inhibited proliferation, migration, and EMT in OSCC cells. HOXC13-AS post-transcriptionally upregulated HOXC13 in OSCC cells. HOXC13-AS mediated malignant phenotypes in OSCC cells through targeting HOXC13. HOXC13-AS induced HOXC13 expression by absorbing miR-378g. Abstract: Oral squamous cell carcinoma (OSCC) is an aggressive cancer type in head and neck. A number of long non-coding RNAs (lncRNAs) are discovered to serve regulatory roles in OSCC. HOXC13 antisense RNA (HOXC13-AS) has been proved to behave as a tumor-facilitator in nasopharyngeal carcinoma, but its regulatory role in OSCC has never been investigated. In this study, GEPIA indicated that HOXC13-AS and its neighbor gene HOXC13 were upregulated in HNSC samples, and we consistently unveiled their upregulation in OSCC tissues and cell lines. Silencing HOXC13-AS abrogated OSCC cell proliferation, migration, and epithelial-to-mesenchymal transition (EMT). Moreover, HOXC13 overexpression rescued the influences of HOXC13-AS silence on OSCC cellular processes and in vivo tumor growth. Mechanistically, HOXC13-AS upregulated HOXC13 expression in OSCC through sequestering miR-378g, which was proved to exert suppressive functions in the malignant behaviors of OSCC cells. Further, HOXC13 was revealed to be positively correlated with HOXC13-AS and negatively with miR-378g in expression in OSCC samples. In sum, our findings suggested that HOXC13-AS functioned as a ceRNA to accelerate the malignant behaviors of OSCC cells via miR-378g/HOXC13 axis, shedding a new light on the lncRNA-targeted treatment for OSCC.